Natural Resource Development and Human Rights in Latin America State and non-state actors in the promotion of and opposition to extractivism - Raftopoulos, Malayna; Powęska, Radosław (HRC series, 2020)
Contemporary development debates in Latin America are marked by the pursuit of economic growth, technological improvement and poverty reduction, and are overshadowed by growing concerns about the preservation of the environment and human rights. This collection's multidisciplinary perspective links local, national, regional and transnational levels of inquiry into the interaction of state and non-state actors involved in promoting or opposing natural resource development. Taking this approach allows the book to contemplate the complex panorama of competing visions, concepts and interests grounded in the mutual influences and interdependencies which shape the contemporary arena of social-environmental conflicts in the region.